Female labour force participation and maternal mortality in Cameroon - Joyce, Kwalar Nkahni; Fonchamnyo, Dobdinga Cletus; Wujung, Vukenkeng Andrew (International Journal of Social and Administrative Sciences, 2024)
The study aimed at analyzing the relationship between female labor force participation and maternal mortality in Cameroon using data from the 2018 Cameroon Demographic and Health Survey. The research employed the Multiple Correspondence Analysis (MCA) to generate an index for maternal mortality. Subsequently, the results were estimated using the Linear Regression with Endogenous Treatment Effects Model (LRETEM) and the ordinary least square. The findings suggested that a woman who engages in the labor market may experience pregnancy-related problems and ultimately pass away. Female labor force involvement was also positively and significantly correlated with maternal mortality. Maternal mortality will rise by 12.9% with every 1% increase in female labor force participation. Maternal mortality was found to be significantly influenced by educational attainment. It was discovered that a rise in education will cause a decrease in maternal mortality in Cameroon, irrespective of educational attainment. Accordingly, the study suggests that evidence-based clinical and programmatic guidelines that support women technically, promote more accessible and efficient treatments, and create suitable guidelines for healthcare professionals can all help lower maternal mortality. Also, governments should equally support healthcare providers to implement policies, through monitoring and mentoring programmes.